2011
DOI: 10.1152/ajpheart.00475.2011
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of embryonic avian blood

Abstract: Shear stress, a mechanical force created by blood flow, is known to affect the developing cardiovascular system. Shear stress is a function of both shear rate and viscosity. While established techniques for measuring shear rate in embryos have been developed, the viscosity of embryonic blood has never been known but always assumed to be like adult blood. Blood is a non-Newtonian fluid, where the relationship between shear rate and shear stress is nonlinear. In this work, we analyzed the nonNewtonian behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Embryonic chick blood has a fairly constant viscosity in the physiological shear rate range [43], so that WSR should be proportional to wall shear stress. Al-Roubaie et al reported small changes in viscosity during later development over large periods of developmental time (4 days) [44], indicating that the changes in viscosity between HH13 and HH18 (20 h) are likely minimal and can be assumed constant.…”
Section: Two-dimensional Structural and Doppler Optical Coherence Tommentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic chick blood has a fairly constant viscosity in the physiological shear rate range [43], so that WSR should be proportional to wall shear stress. Al-Roubaie et al reported small changes in viscosity during later development over large periods of developmental time (4 days) [44], indicating that the changes in viscosity between HH13 and HH18 (20 h) are likely minimal and can be assumed constant.…”
Section: Two-dimensional Structural and Doppler Optical Coherence Tommentioning
confidence: 99%
“…We used four-dimensional embryo-specific geometries of the OFT lumen (segmented from OCT images), which consisted of a sequence of meshes that depicted the dynamic motion of the OFT walls over the cardiac cycle. Blood was modelled as a Newtonian fluid having density r ¼ 1060 kg m 23 [43] and viscosity m ¼ 0.003 Pa s. Embryo-specific blood flow through the OFT was modelled using a recently developed inverse method based optimization procedure [45]. Briefly, normal tractions (pressures) at the OFT lumen inlet and outlet surfaces (or more practically their difference) were iteratively imposed, until computed and measured Doppler velocities at an optimization point in the interior of the lumen differed by less than 1%.…”
Section: Embryo-specific Four-dimensional Computational Fluid Dynamicmentioning
confidence: 99%
“…We were obliged, however, to extrapolate our previous viscosity data with respect to embryonic stage. Our previous results had shown that there was no change in apparent viscosity of blood with respect to stage when the haematocrit is below 50% (Al-Roubaie et al, 2011). Therefore, extrapolation results in similar values for the viscosity as using the data directly for the older embryos.…”
Section: Discussionmentioning
confidence: 57%
“…The data was fit to a cubic equation as a means to easily calculate the haematocrit in our computational analysis. We previously published values for the viscosity of avian blood at different shear rates and haematocrits for embryos between 4 days and 6 days of incubation, or HH22 to HH34 (Al-Roubaie et al, 2011). Embryos used in this current work were much younger, starting at 30 h of incubation (13 somites or HH11).…”
Section: Viscosity Estimates In Embryonic Vesselsmentioning
confidence: 99%
See 1 more Smart Citation